Adeonellas from the Gulf of Aden including one new species - Amui, Ann-Margret (Zootaxa, 2005)
The genus Adeonella Busk, 1884 consists of 41 species, with a broad distribution in the southern hemisphere. Just three are known from the east African coast so far: A. distenta from the coast of Aden, A. lichenoides and A. falcicuala from Zanzibar (Hayward 1988). Hayward (1983) suggested that further species of Adeonella are likely to be found along the east African coast. Two species of Adeonella, including one new species, are reported from the Gulf of Aden in this study.